PENGARUH JENIS ASAM DAN SUHU EKSTRAKSI TERHADAP KARAKTERISTIK PEKTIN DARI KULIT PISANG KEPOK - yuli ristianingsih; Indriana Lestari; Wibiana Wulan Nandari (Eksergi, 2021)
Pectin is structurally and functionally the most complex polysaccharide in plant cell walls. Pectin is widely used as an adhesive and emulsifier in the food, pharmaceutical industry and also as an adsorbent in waste water treatment. This research used banana peels as a raw material. The purpose of this study was to study the effect of temperature and solvent (acetic acid and hydrochloric acid) on the characteristics of pectin (ash content, methoxyl and galacturonic content). This research was carried out in a stirred tank reactor for 90 minutes with various types of solvents (hydrochloric acid and acetic acid) and extraction temperatures (60, 70, 80 and 90) 0C. Based on the research, it was found that the optimum pectin yield with 0.25 N HCl at a temperature of 800C was 24.93%. The characteristics of pectin which include galacturonic acid, methoxyl content, ash content and equivalent weight at an extraction temperature of 800C with a concentration of 0.25 N HCl were 79,56%; 2.65; 6,72% and 3846